Shift work and shift work sleep disorder: Medical and Psychiatric implications due to shift work - Dr. M. Asarnisa Begum (Tamil Psychiatry Journal, 2025)
Shift work has been around for a long time, and various employees in the medical sector, transportation sector, emergency services, police and IT sector have been working on shift basis. Some industrial companies are also practicing shift work to increase their productivity. In the IT sectors where such jobs are paid lot more, and where one can also work part-time while studying, the number of part-time jobbers and shift workers have increased significantly. Eight hours of sleep per day is necessary for an adult, who has reached the age of 18 years, to remain physically and mentally fit and healthy. But the shift work causes irregular sleep cycle and various other negative changes in the internal metabolism, homeostasis as well as external behaviour of an individual. Researches have shown that shift workers have a significant decline in individual’s work performance and cognitive abilities. In this context, this article discusses the changes in mental health, physical health and sleep cycle caused by shift work. It also discusses the impact of shift work on a person with mental illness. Some of the evidence based practical strategies on how shift workers can manage their sleep routine and thereby reduce the impact of sleep deprivation, are also discussed here.